2016
DOI: 10.1002/ijop.12387
|View full text |Cite
|
Sign up to set email alerts
|

Hard times and European youth. The effect of economic insecurity on human values, social attitudes and well‐being

Abstract: While economic downturns have adverse effects on young people's life chances, empirical studies examining whether and to what extent human values, social attitudes and well‐being indicators respond to sudden economic shocks are scarce. To assess the claim that human values are less affected by economic shocks than social attitudes and well‐being, two distinct yet related studies based on the European Social Survey (ESS) are conducted. The first employs a fixed effects pseudo‐panel analysis of the 2008–2014 ESS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
2
25
0
2
Order By: Relevance
“…In line with Schwartz's theory, which posits that personal values are socialized at an early age and are mostly stable and context independent for the rest of one's life, Reeskens and Vandecasteele (2016) found little impact of the economic crisis on values in the ESS data. However, they also found that some values related to social support and social interaction are more likely to be affected by specific life conditions and periods of economic hardship.…”
Section: Contextual Influences On Protest Behaviourssupporting
confidence: 70%
“…In line with Schwartz's theory, which posits that personal values are socialized at an early age and are mostly stable and context independent for the rest of one's life, Reeskens and Vandecasteele (2016) found little impact of the economic crisis on values in the ESS data. However, they also found that some values related to social support and social interaction are more likely to be affected by specific life conditions and periods of economic hardship.…”
Section: Contextual Influences On Protest Behaviourssupporting
confidence: 70%
“…Using the European Social Survey, they examine both aggregate‐level population data and individual level data, showing that, as expected, values underscoring openness to new experiences or emphasising self‐restriction and order remain resistant in the face of sudden economic shocks. Likewise supporting prior expectations, declines in political trust and in satisfaction with the economy in the face of economic risk show the response of these social attitudes to the experience of economic hardship (Reeskens & Vandecasteele, ). However, counter to their expectations they find that social trust is less affected by changes in national youth unemployment rates, suggesting that it is less dependent on situational conditions and less volatile than political trust and satisfaction with the economy.…”
Section: Multiple Dimensions Of Adjustment In Young Adulthoodmentioning
confidence: 66%
“…Positive self‐views are found to be associated with a person's overall life satisfaction, well‐being and mental health, even after controlling for the experience of socio‐economic risk and disadvantage (Trzesniewski et al, ). Regarding the effects of the recession on young people's self‐views and subjective perceptions of well‐being, the research reported in this special section finds that the demands of the recession slowed the development of positive self‐views among adolescents (Johnson et al, ), among general population samples (Reeskens & Vandercasteele, ), and among undergraduate students (Park et al, ). Moreover, the recession was linked to increases in depressed mood (Johnson et al, ) and lowered levels of subjective health (Reeskens & Vandercasteele, ).…”
Section: Multiple Dimensions Of Adjustment In Young Adulthoodmentioning
confidence: 95%
See 2 more Smart Citations